The house of Hades - Riordan, Rick. (New York : Hyperion Books, 2013)
"Greek and Roman demigods from the Prophecy of Seven must work together to seal the Doors of Death--and help Percy and Annabeth escape the Underworld in the process"--
Keywords: Mythology, Roman; Mythology, Greek; Giants; Camps; Hera (Greek deity).; Gaia (Greek deity).; JUVENILE FICTION / Legends, Myths, Fables / Greek & Roman